Prostaglandin E2 and nitric oxide mediate the acute inflammatory (erythemal) response to topical 5‐aminolaevulinic acid photodynamic therapy in human skin. (30th August 2013) - Brooke, R.C.C.; Sidhu, M.; Sinha, A.; Watson, R.E.B.; Friedmann, P.S.; Clough, G.F.; Rhodes, L.E.
<x xml:space="preserve">Abstract</x> What's already known about this topic? An acute inflammatory response is clinically observed following topical 5‐aminolaevulinic acid (ALA) photodynamic therapy (PDT). Histamine mediates the immediate reaction, but the mediators of the prolonged erythemal response are unknown. Prostaglandin (PG)E2 and nitric oxide (NO) are released following PDT in experimental models, where they can influence the therapeutic response to PDT. What does this study add? PGE2 and NO are released in healthy human skin following topical 5‐ALA‐PDT. The role of these mediators in the clinical inflammatory response of human skin to 5‐ALA‐PDT is demonstrated by the application of topical inhibitors. The potential significance of these mediators in the response to PDT in human cutaneous pathology warrants study.